LEGALITAS INTERVENSI RUSIA TERHADAP UKRAINA (STUDI KASUS KRIMEA) - Mochammad Havis Yanuar; Sasmini Mintorodihardjo (BELLI AC PACIS, 2015)
This study was conducted to determine the legality of the Russian intervention on the territory of Crimea in Ukraine. Researcher answer the problem with normative side by basing on the norms and principles of intervention. Materials used in this research include international agreements, doctrine, customary international law, as well as some cases of intervention. Legal materials collected through library research and analyzed through content analysis and text interpretation. The results showed that the legality of intervention discussion is based on five criteria namely: collective intervention by the UN charter, intervene to protect the interests and rights of citizens in other countries, intervention as self-defense, state intervention protectorate, and intervene if a country committed serious violations. So the Russian intervention on the territory of Crimea not obtain legality because it does not meet the five criteria for intervention is allowed in international law.